A manifestation of the divine world’s beauty through the human’s creativity, or a possibility of the “ontological conversation” (st. Gregory Palamas and P. Florensky) - Василенко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article investigates the foundations of the “broken ontology” transfiguration, which connect St. Gregory Palama`s and P. Florensky`s philosophical ways.